Solid–Liquid Interfacial Coordination Chemistry Enables High‐Capacity Ammonium Storage in Amorphous Manganese Phosphate - Yang, Duo; Song, Yu; Zhang, Ming‐Yue; Qin, Zengming; Liu, Jie; Liu, Xiao‐Xia (Angewandte Chemie International Edition, 2022)
Ammonium (NH4+) ion as charge carrier is attracting attention in aqueous batteries. Yet, most NH4+ host materials are still limited by the relatively low capacities. Here, we fabricated a manganese phosphate (MP‐20) for NH4+ ion storage. MP‐20 displays a high capacity of 299.6 mAh g−1 at 1 A g−1 in ammonium acetate (NH4Ac) electrolyte, outperforming other reported NH4+ host materials. Spectroscopy studies suggest a new NH4+/H+ co‐insertion mechanism. We surprisingly discover that the NH4Ac electrolyte plays an important role in improving the charge storage capability of the materials. Experimental and computational results indicate acetate ions can form coordination bonds with the Mn atoms, tailoring the electronic structure of the Mn atoms and the surrounding O atoms, and therefore facilitating the NH4+ storage process. Our findings provide a new NH4+ host material and propose the important role of the electrolyte‐electrode coordination effect in aqueous ammonium batteries. An amorphous manganese phosphate material is prepared using an electrochemical method for aqueous NH4+ ion storage. The electrode displays an ultra‐high capacity of 299.6 mAh g−1 at a current density of 1 A g−1 in NH4Ac electrolyte. Acetate ions can coordinate with the Mn sites and tailor the surface properties of the electrode, leading to the enhanced NH4+ adsorption capability.